Sustained BOLD and theta activity in auditory cortex are related to slow stimulus fluctuations rather than to pitch - Steinmann, Iris; Gutschalk, Alexander (Journal of neurophysiology, 2012)
Human functional MRI (fMRI) and magnetoencephalography (MEG) studies indicate a pitch-specific area in lateral Heschl's gyrus. Single-cell recordings in monkey suggest that sustained-firing, pitch-specific neurons are located lateral to primary auditory cortex. We reevaluated whether pitch strength contrasts reveal sustained pitch-specific responses in human auditory cortex. Sustained BOLD activity in auditory cortex was found for iterated rippled noise (vs. noise or silence) but not for regular click trains (vs. jittered click trains or silence). In contrast, iterated rippled noise and click trains produced similar pitch responses in MEG. Subsequently performed time-frequency analysis of the MEG data suggested that the dissociation of cortical BOLD activity between iterated rippled noise and click trains is related to theta band activity. It appears that both sustained BOLD and theta activity are associated with slow non-pitch-specific stimulus fluctuations. BOLD activity in the inferior colliculus was sustained for both stimulus types and varied neither with pitch strength nor with the presence of slow stimulus fluctuations. These results suggest that BOLD activity in auditory cortex is much more sensitive to slow stimulus fluctuations than to constant pitch, compromising the accessibility of the latter. In contrast, pitch-related activity in MEG can easily be separated from theta band activity related to slow stimulus fluctuations.